ChemInform Abstract: Elusive 2H‐1, 2‐Oxasiletes Through Reactions of an Isolable Dialkylsilylene with Diazocarbonyl Compounds. Issue 3 (29th December 2015) - Dong, Zhaowen; Xiao, Xu‐Qiong; Li, Zhifang; Lu, Qiong; Lai, Guoqiao; Kira, Mitsuo
Abstract: Novel 2H‐1, 2‐oxasiletes (III) are obtained in high yields by reaction of diazocarbonyl compounds (I) with dialkylsilylene (II), whilst diazoketone (IV) leads to spirocyclic adduct (V) without releasing dinitrogen.